Kontribusi Denominasi Lutheran Dalam Membentuk Pendidikan Finlandia Dan Pemikirannya Bagi Pendidikan Kristen - Gultom, Yohansen Wyckliffe (JURNAL DIAKONIA, 2023)
This study describes the historical and theological influence of Martin Luther's Protestant reform movement on education in Finland. The Church's role in congregational catechisation, starting with education for priests and developing later for the congregation, had implications for the congregation's desire to learn new things. The thinking of Martin Luther and Philipp Melanchton also impacted on the ongoing reformation movement to think about congregational education. As a result, educational facilities ranging from schools, libraries and educational methods were thought of by reformers after Luther, in Finland. Until, the basic principles of Lutheran thought are also guided either consciously or unconsciously in modern Finnish education. This research is a qualitative research with data collection techniques through literature study. The results of the study show that there is a theological continuity in Finnish educational practices after Luther's Reformation Movement in 1517, with implications for congregational catechisation, growing interest in learning, the availability of educational facilities by the Church to develop modern educational methods in Finland. Keywords: State and Religion; Protestant Reformation; Finnish Christian Education